(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Employers today view their workforce as multi-competent, having moved away from a model where workers only knew one competence. To monitor employee performance and foster career development, organizations are interested in learning about the current skill level of their workforce. Competency mapping becomes important in this situation. Finding the key employee competency elements influencing job performance was the aim of this study. Creating a scale for "competency-based superior performance" and validating an employee performance scale were part of the research strategy. Using a standardized questionnaire, 730 respondents provided the data for this study. The study’s primary hypothesis is to determine the key employee competency elements impacting job performance as well as the link between employee competency and job performance. Thus, the present study examined the relationship between employee competency and job performance as well as the competency elements influencing job performance among Tamil Nadu’s Western District auto component manufacturers.